Kinship Trees: Image and Legal-Theological Thought in the New World - Mejía Quiroga, Pilar; Soler, Ana Isabel (Eikón / Imago, 2023)
The article examines the relationships between the legal doctrine on the bonds of consanguinity and affinity, and the debates on the validity of marriage among indigenous peoples, from the perspective of their different visual representations. Thus, it explores both the graphics designed in the legal literature, as well as those tree-like representations that can be found in files and chronicles of local native populations. It also pays special attention to the impact of printing techniques on the emergence of graphic representations and their huge implications in legal-theological thought. Finally, the article reflects on the organic metaphor and the use of visual tools in canon law, in order to understanding the transformations that kinship trees underwent when they were used, translated and reproduced in new contexts and their materialities.